The economics of college sports: cartel behavior vs. amateurism - Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2006)
This paper studies intercollegiate athletics in the context of the theory of cartels. Some point to explicit attempts by the National Collegiate Athletic Association (NCAA) to restrict output and payments for factors of production as evidence of cartel behavior. Others argue that such limits enhance product quality by preserving amateurism. I find that the NCAA's compensation limits on athletes lead to high levels of rents from the entertainment revenues produced by the athletes. The athletes producing these rents are disproportionately African-American, while the beneficiaries are primarily white. The rents are typically spent on coaches' salaries, facilities, and nonrevenue sports. Although athletic departments considered as businesses lose money on average, there is some evidence, although not unanimous, that they generate alumni contributions, state appropriations, and additional student applications.
Keywords: L12; L44; I21; 330; cartel; monopsony; college athletics